Perspectives of implementation of solar water heaters of sanitary-household purpose in Republic of Moldova - Ermuratskii V.V.; Postolaty V.M.; Koptiuc E. (Problems of the Regional Energetics)
The mathematical model of a heating system of the multi-storied house is developed, allowing solving a problem of distribution between apartments of heat of the centralized heat supply. It is taken into account own independently developed heat, which is determinate by means of individual counters of gas and the electric power. Basic feature of model is the opportunity of the account of mutual heat exchange between apartments.